The Symbiotic Effect of a New Nutraceutical with Yeast β-Glucan, Prebiotics, Minerals, and Silybum marianum (Silymarin) for Recovering Metabolic Homeostasis via Pgc-1α, Il-6, and Il-10 Gene Expression in a Type-2 Diabetes Obesity Model - Aline Boveto Santamarina; Ruan Carlos Macêdo Moraes; Victor Nehmi Filho; Gilson Masahiro Murata; Jéssica Alves de Freitas; Danielle Araujo de Miranda; Anderson Romério Azevedo Cerqueira; Soraia Katia Pereira Costa; Ana Flávia Fernandes Ferreira; Luiz Roberto Britto; Juliana Alves de Camargo; Daniela Rodrigues de Oliveira; et al. (MDPI AG, 2022)
The use of natural products and derivatives for the prevention and control of non-communicable chronic diseases, such as type-2 diabetes (T2D), obesity, and hepatic steatosis is a way to achieve homeostasis through different metabolic pathways. Thus, male C57BL/6 mice were divided into the following groups: high-fat diet (HFD) vehicle, HFD + Supplemented, HFD + Supplemented_S, and isolated compounds. The vehicle and experimental formulations were administered orally by gavage once a day over the four weeks of the diet (28 consecutive days). We evaluated the energy homeostasis, cytokines, and mitochondrial gene expression in these groups of mice. After four weeks of supplementation, only the new nutraceutical group (HFD + Supplemented) experienced reduced fasting glycemia, insulin, HOMA index, HOMA-β, dyslipidemia, ectopic fat deposition, and hepatic fibrosis levels. Additionally, the PPARγ coactivator 1 α (Pgc-1α), interleukin-6 (Il-6), and interleukin-10 (Il-10) gene expression were augmented, while hepatic steatosis decreased and liver parenchyma was recovered. The glutathione-S-transferase activity status was found to be modulated by the supplement. We discovered that the new nutraceutical was able to improve insulin resistance and hepatic steatosis mainly by regulating IL-6, IL-10, and Pgc-1α gene expression.